Pengaruh Kepadatan Benih dan Sistem Transportasi Basah Tertutup Terhadap Kelangsungan Hidup PL12 Udang Vaname - Edy Suprayitno; Sri Oetami Madyowati; Achmad Kusyairi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aimed to evaluate the effect of post-larvae (PL) 12 density of whiteleg shrimp (Litopenaeus vannamei) on survival during transportation using a closed wet system. The study was conducted experimentally using four different density treatments: 500, 750, 1000, and 1250 shrimp per liter of water. The purpose of these density variations was to identify the optimal density level that still ensured a high survival rate during transportation. The results showed that shrimp seed density significantly influenced survival. A density of 500 shrimp/liter resulted in the highest survival rate of 99.6%, while a density of 1250 shrimp/liter showed the lowest survival rate of 99.30%. Although the differences in numbers appear small, the ANOVA statistical test showed that the differences between the treatments were significant. These results were reinforced by a further LSD (Least Significant Difference) test, which confirmed significant differences between treatment groups. In addition, water quality parameters such as dissolved oxygen, temperature, and pH were also observed during transportation. Measurement results showed that dissolved oxygen and temperature changed significantly with increasing seed density. However, pH did not show any significant differences between treatments. Overall, the results of this study indicate that shrimp seed density and water quality parameters are important factors to consider in the shrimp fry transportation system. Appropriate density management can minimize stress and mortality, and ensure seed survival during the distribution process.